1995
DOI: 10.1139/x95-052
|View full text |Cite
|
Sign up to set email alerts
|

Juniperusoccidentalis juvenile foliage: advantages and disadvantages for a stress-tolerant, invasive conifer

Abstract: Physiological processes for juvenile and adult foliage of Juniperusoccidentalis Hook. were compared to evaluate the advantages and disadvantages of juvenile foliage for a stress-tolerant, invasive conifer. Above- and below-ground biomass allocation and monthly measurements (April through October) of gas exchange, water relations, foliar nitrogen concentrations, and growth were made for juvenile and small-adult trees in the field in central Oregon. Compared with small adults, juveniles have greater allocations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 0 publications
3
33
0
3
Order By: Relevance
“…Yet, provenances from dry regions show a consistently longer juvenile phase (López et al 2007). This counter-intuitive outcome was also found in Juniperus occidentalis (Miller et al 1995). Juniperus occidentalis is a water stress-tolerant species that maintains the juvenile vegetative state as a strategy to enhance its competitive ability.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Yet, provenances from dry regions show a consistently longer juvenile phase (López et al 2007). This counter-intuitive outcome was also found in Juniperus occidentalis (Miller et al 1995). Juniperus occidentalis is a water stress-tolerant species that maintains the juvenile vegetative state as a strategy to enhance its competitive ability.…”
Section: Introductionmentioning
confidence: 73%
“…Intervals are standard errors. pna: P. pinea, bru: P. brutia, can : P. canariensis, rad: P. radiata; hal: P. halepensis, nig: P. nigra, ptr: P. pinaster, syl: P. sylvestris, unc: P. uncinata (Miller et al 1995;Darrow et al 2002). Our results support that the species from drier habitats tend to delay heteroblastic change, and this is generally related to lower cuticular transpiration of adult needles and higher differentiation between juvenile and adult foliage types (see correlations in Table 5).…”
Section: Adultmentioning
confidence: 99%
See 2 more Smart Citations
“…dles (Jimenez et al, 2000), which was confirmed in Juniperus occidentalis (Miller et al, 1995) but still not investigated in pines. However, while previous research have shown that secondary needles have a significantly lower cuticular transpiration than primary needles in this species (Climent et al, 2006), our experiment revealed similar susceptibility to frost injury which suggest different tolerance pathways between drought and cold.…”
Section: P C a N A R Ie N S Is P R A D Ia T A P P In E A P H mentioning
confidence: 90%